Hubungan Indeks Massa Tubuh Terhadap Dosis Radiasi Pada Angiografi Koroner - Sumarsono, Sumarsono; Musdalifah, Indah (Lontara Journal of Health Science and Technology, 2020)
the world. Ionizing radiation-based diagnostic and therapeutic procedures are increasingly being used in daily clinical practice, especially in cardiology during coronary angiography. The health risks of radiation are well known. Obesity has now become an epidemic. To investigate whether the patient's Body Mass Index (BMI) has an effect on the radiation dose received by the patient during diagnostic coronary angiography. This study was an analytical observational study with a cross sectional study design to analyze the dose parameters of 48 patients who underwent coronary angiography procedures in the cardiac catheterization laboratory. Patient clinical radiation dose data in the form of kerma-area-product (DAP) and air-kerma at the intervention reference point (Ka, r) with information on the patient's height and weight to calculate the body mass index value. The data obtained were analyzed using Pearson Correlation. The statistical test conducted shows that the value of BMI against DAP and KERMA has a P-value of 0.003 and 0.006, respectively. Because P-vaue is less than ? = 0.01, there is a significant linear relationship between BMI and DAP values as well as BMI and KERMA. Obese patients require higher radiation doses than those with a normal BMI. Thus it can be used as a reference for increasing the radiation dose when performing the procedure in patients with increased BMI.